EMOTIONAL FREEDOM TECHNIQUES (EFT) MENURUNKAN KECEMASAN SISWA MENGHADAPI UJIAN AKHIRNASIONAL - Wahyu Hidayati, Rizqi; Huriah, Titih (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Introduction: National Final Examination (UAN) often gives psychological impacts for students,especially anxiety. If anxiety is allowed to continue, it will give negative impacts on teens, such as adecision to commit promiscuity. Therefore, there are needs for therapies that can reduce the anxiety ofstudents in facing exam, one of which is Emotional Freedom Techniques (EFTs). Objective: To determine the effect of EFT on anxiety in the face of UAN at high school students. Methods:The research method was quasi experimental with pretest-posttest design. Prior to therapy, anxiety screening was performed on 137 students using a questionnaire of Pasco-Hernando CommunityCollege (PHCC) Anxiety Test. After that, 28 were taken students as the sample divided into 2 groups (control and intervention), each 14 students. The intervention group received 3 times of EFT therapysessions. Analysis of data was to determine the effect by using a paired t-test and to know thecomparison used independent t-test, with a of 0.05. Results:The initial screening results were as follows: mild to moderate anxiety (58, 4%) and moderate tosevere anxiety (0.7%). Test results of paired t-test showed p = 0, 046 (p <0, 05). In addition, based onindependent t-test, p was 0.000 (p <0.05); thus, the mean value of anxiety of the intervention group wassignificantly lower than that of the control group. Conclusion: EFT effectively reduced student anxiety in facing UAN in SMA N 1 Pakem, Sleman,Yogyakarta. It is suggested EFT can be used as a non-pharmacological psychological therapy. Keyword: EFT, anxiety, adolescents